(untitled) (Journal of Nepal Geological Society, 2011)
All formations (Kuncha Formation, Fagfog Quartzite, Dandagoan Phyllite, Nourpul Formation, Dhading Dolomite of the Lower Nawakot Group and Benighat Slate, Malekhu Limestone and Robang Formation of the Upper Nawakot Group) of the Nawakot Complex are well exposed along the Malekhu-Thopal Khola and Galchi - Kaljeri section s, west of the Kathmandu Valley. The Phalangu Khola and Syabrubensi sections, north of the Kathmandu Valley do not show the exposures of all formations (exposures of the Kuncha Formation, Fagfog Quartzite, and Benighat Slate only). The stratigraphic sequences from the Kuncha Formation to Dhading Dolomite (Lower Nawakot Group) along the Malekhu-Thopal Khola section are overturned, showing the younging strata to the deeper sections shown by the sedimentary structures (ripple marks, mudcracks, etc.) and stromatolites. The se overturned sequences could be related to the development of the post Main Central Thrust (MCT)/Mahabharat Thrust (MT) deformational structure (Gorkha - Pokhara anticlinorium, Likhu Khola anticline). The stratigraphic sequences are normal in the formations of the Upper Nawakot Group along the Malekhu-Thopal Khola section. This normal sequence can be also observed along the Galchi - Kaljeri, Phalangu Khola and Syabrubensi sections. In the northern part of the study area along the Likhu Khola, Tadi Khola, Phalangu Khola and Syabrubensi sections, the rocks of the Benighat Slate just below the MCT are highly sheared, deformed, metamorphosed with the development of the garnet and staurolite (medium amphibolite facies metamorphism) due to the movement of the MCT. However, these minerals are not developed in the Robang Formation (immediate below the MT) along the Malekhu-Thopal Khola and Galchi - Kaljeri sections. This formation could be caused by shallow depth metamorphism (green-schist to lower amphibolite facies) along the movement of the MT.